Thermally bandwidth-controllable reflective liquid crystal film from rupture and self-assembly of hydrogen bonds. Issue 12 (25th September 2016) - Wang, Feifei; Song, Ping; Yang, Huai; Shao, Xibin
ABSTRACT: A cholesteric liquid crystal (Ch-LC) composite containing a hydrogen bond (H-bond) chiral dopant (HCD) was prepared and filled into a planar treated cell. When the cell was heated, the selective reflection of the cell exhibited an unusual red shift. One of the reasonable mechanisms was that the H-bonds of HCD ruptured when the temperature was high, and the HCD split into two new chiral dopants (CDs), which made the whole helical twisting power (HTP) value in the composite changed a lot, thus the pitch length of the composite changed. On the basis of this mechanism, when the composite was polymerised at the temperature of H-bonds of HCD ruptured, the bandwidth of the obtained film can be tuned form wider to narrower reversibly by the rupture and self-assembly of H-bonds chiral molecules as the temperature changed, respectively. GRAPHICAL ABSTRACT: